Analysis of the Impact of Financial Performance on the Stock Prices of Publicly Traded Islamic Banks with Interest Rate as a Moderating Variable - Kodri, Kodri; Yudiana, Fetria Eka (Talaa : Journal of Islamic Finance, 2024)
This study aims to analyze the impact of financial performance on the stock prices of publicly traded Islamic banks, with interest rates as a moderating variable. The focus of this research is on Islamic banks in Indonesia listed on the Indonesia Stock Exchange during the period 2018 to 2023. The independent variables used in this study are the financial performance of Islamic banks measured by Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR). The dependent variable is the stock prices of Islamic banks, while the interest rate is used as a moderating variable. Data collection was conducted through the analysis of financial reports of Islamic banks and Islamic stock index data. The results of the study indicate that financial performance has a significant impact on the stock prices of Islamic banks, and interest rates strengthen this effect. This research is expected to contribute to investment decision-making in the Islamic banking sector and provide insights for Islamic banks to improve their financial performance.